Xerxes and Babylonia : The Cuneiform Evidence - Waerzeggers, Caroline; Seire, Maarja; Waerzeggers, Caroline; Seire, Maarja (Leuven Peeters, 2018)
In the summer of 484 BCE Babylonia revolted against Xerxes, king of Persia. In recent years, a debate has crystallized around the nature of Xerxes$1 (Bresponse to this challenge. This volume continues and expands this debate. It collects nine essays on the cuneiform text corpus dated to the period before, during and after the revolts. This material enables the authors to evaluate the nature of Xerxes$1 (Bpolicies in the sphere of society, science, religion, law, administration and economy against the long-term history of the region. The contributions are by Paul-Alain Beaulieu, Johannes Hackl, Michael Jursa, Karlheinz Kessler, Mathieu Ossendrijver, Reinhard Pirngruber, Malgorzata Sandowicz and Caroline Waerzeggers.s
English
Keywords: Ancient history: to c 500 CE; Xerxes; Babylonia; Persia; cuneiform texts; ancient history